The relationship between body mass index and clinical complications among patients undergoing myomectomy - Gürbüz, Tuğba; Yardımcı, Oğuz; Udum, Sertaç; Günay, Taner (Journal of Surgery and Medicine, 2020)
Aim: Obesity, a chronic disease which significantly causes disability, is a critical public health concern all over the world. A possible correlation between the complications of uterine leiomyoma and obesity has been recently considered, but no definitive conclusions have been made. The purpose of this study is to investigate the association between body mass index (BMI) and clinical complications among the patients undergoing myomectomy to see whether BMI can affect the clinical outcomes and complications of women with uterine leiomyoma. Methods: This retrospective cohort study was conducted on the patients undergoing abdominal myomectomy for uterine leiomyoma from September 2016 to December 2019. A total of 287 patients undergoing abdominal myomectomy participated in the study. The patients were divided into two groups based on BMI: BMI <30 kg/m2 (Group 1) and BMI 30 kg/m2 (Group 2). Results: The mean ages of the patients in Groups 1 and 2 were 37.08(6.17) years and 37.53 (5.98) years, respectively. Among all, 196 patients had a BMI of <30 kg/m2 and 91 patients had a BMI of 30 kg/m2. There was no statistically significant difference between the two groups in terms of surgical indication (P=0.970), leiomyoma localization (P=0.793), leiomyoma size (P=0.335), the mean number of fibroids removed (P=0.537), postoperative pathological diagnosis (P=0.189), complications, and the mean duration of hospital stay (P=0.249). There was a statistically significant difference between the two groups in terms of BMI (P<0.001), ALT (P=0.039), and Urea (P=0.018). Conclusion: BMI did not adversely affect the clinical outcomes of patients undergoing abdominal myomectomy. Obesity is not regarded as a risk factor for poor outcomes.